The conversation [videorecording (DVD)] - Sedlar, Dominik; Phillipson, Caspar; Turner, Dylan; Pincic, Doris (Deskpop Entertainment, 2024)
Based on a true story of a conversation that shaped the world in 1945 between two powerful men with opposing perspectives on the future of their country. It was a dangerous time; the Partisans had won the war, and the Red Army was nearby.